Intra-Industry Trade in Manufacturing Supply Chain: An Empirical Assessment of the India-ASEAN Case - Anupama Devendrakumar Masali (International Journal of Supply Chain Management, 2016)
The purpose of the paper is to examine the patterns and to assess the determinants of India's Intra-Industry Trade (IIT) in manufacturing supply chain withsix major ASEAN economies from the inception of formal economic arrangements in 1993 to the year 2013. The study assesses IIT in manufacturing supply chain for six diverse country pairs. The findings have significant implications for the current inadequate 'top-down' approach and the missing complementary 'bottom-up' approach to deepen ASEAN-India regional economic integration. ASEAN-India trade in manufacturing supply chain increased considerably over the past two decades but studies examining the nature and the patterns are few. The paper provides a novel examination of the hitherto uninvestigated India's IIT in manufacturing supply chain with individual ASEAN countries over two decades. The anlaysis juxtaposes six country pairs within a frame, enabling an emphasis on the contrasts across six diverse ASEAN countries in the manufacturing supply chain.